Paving Block Quality With Several Types of Plastic Waste on Compressive Strength - Cahyani, Risti Indah; Irfaniyah, Dina; Alfarizki, Ahmad Fikri; Kusumah, Fuji Hernawati (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Pollution in Indonesia has increased over time due to the large amount of waste that is not managed properly, one of which is plastic waste which has a negative impact on the environment, where it can pollute oceans, rivers and other environmental areas. On the other hand, the increase in natural resources and community needs are also increasing rapidly. So, based on these problems, this research aims to utilize plastic waste as a mixture to form paving blocks and analyze the quality of paving blocks better. The method used in this research is experimental which is carried out by making paving blocks with different types of plastic, namely PET ( polyethylene ethylene terephalate ) , PP (polypropylene) and PS (polystyrene plastic) with a mixture of gravel with a weight volume ratio of 50: 50. Model The paving blocks studied were paving blocks in the form of blocks with object dimensions measuring 14.5 Ã— 9.5 cm x 3.5 cm. The results of the research showed that the compressive strength of PP, PET and PS plastic types were 33.8 MPa, 18 MPa, and 9 MPa respectively. Thus, it can be concluded that the PP (polypropylene) plastic mixture has the best quality in handling quite heavy loads.